Model PBL dengan Media Asesmen AR: Pengaruh Keterampilan Berpikir Kritis dan Hasil Belajar - Hidayah, Hikmah; Maryani, Maryani; Nuraini, Lailatul (U-Teach: Journal Education of Young Physics Teacher, 2025)
The purpose of the research was to examine the effect of implementing the Problem Based Learning model accompanied by Augmented Reality assessment media on critical thinking skills and physics learning outcomes in high school on circular motion material. This research uses the type of research true experiment because the research sample was selected using a lottery technique or randomly. The sample was obtained by testing the homogeneity of the midterm exam scores that had been carried out by the teacher. The research design used posttest only control group design. Based on the results of the Mann-Whitney U Test, it can be found that Asymp. Sig (2-tailed) of 0.028 <0.05. This shows that H0 is rejected and Ha is accepted. Proving that there is an effect of the implementation of Problem Based Learning models accompanied by Augmented Reality assessment media on students' critical thinking skills in circular motion material. And the results of the T test (Independent Sample T-Test) found that Asymp. Sig (2-tailed) of 0.006 <0.05, then H0 is rejected and Ha is accepted, then it is concluded that the implementation of Problem Based Learning models accompanied by Augmented Reality assessment media affects student learning outcomes in circular motion material. Furthermore, there are suggestions for other researchers, namely that they can use the results of this study as a reference and basis for exploring other topics or materials and developing interactive learning media that are interesting, innovative and more creative